Investigation into the Synergistic Effects of Sediment Concentration and Particle Size on the Friction and Wear Properties of Nitrile Butadiene Rubber - Lun Wang; Xincong Zhou; Qipeng Huang; Xueshen Liu; Zhenjiang Zhou; Shaopeng Xing (Journal of Marine Science and Engineering)
Nitrile Butadiene Rubber (NBR) is commonly used in ships’ water-lubricated tail bearings. However, sediment in the water significantly affects these bearings’ friction and wear performance. This study investigates NBR test blocks’ friction and wear behavior in conjunction with ZCuSn10Zn2 copper ring friction pairs within a sediment-laden water lubrication environment. Two primary factors were considered: sediment particle concentration and sediment particle size. Friction and wear tests were conducted under pure water and sediment-laden conditions using the ZY-1 ring block friction and wear tester. The friction coefficients, wear quantities, and variations in mass concentrations and sediment particle sizes were measured and compared. The surface morphology of the test blocks was analyzed using a laser confocal microscope. The findings indicate that as sediment concentration increases, the particle size’s impact on NBR’s abrasive wear diminishes. The variation in particle size directly influences the number of particles that penetrate the interface between the friction partners and the nature of three-body wear. Conversely, changes in particle concentration primarily affect the extent of wear; specifically, both the wear volume and the average coefficient of friction of the NBR specimens increase with rising sediment concentration. The wear mechanisms observed on the surface of the NBR test blocks are predominantly characterized by micro-cutting, rolling wear, and the coexistence of both wear modes. This study offers valuable insights for the design and optimization of water-lubricated bearings.